DNA damage and cytotoxicity induced on common carp by pollutants in water from an urban reservoir. Madín reservoir, a case study. (October 2017) - Pérez-Coyotl, I.; Martínez-Vieyra, C.; Galar-Martínez, M.; Gómez-Oliván, L.M.; García-Medina, S.; Islas-Flores, H.; Pérez-Pasten Borja, R.; Gasca-Pérez, E.; Novoa-Luna, K.A.; Dublán-García, O.
Abstract: Madín Reservoir provides a substantial amount of drinking water to two municipalities close to Mexico City metropolitan area. However, it receives untreated wastewater discharges from domestic sources in the towns of Nuevo Madín and others, as well as diverse pollutants which are hauled by the Río Tlalnepantla from its upper reaches, so that the xenobiotics in the reservoir are highly diverse in terms of type and quantity. Previous studies showed that MR is contaminated with xenobiotics such as Al, Hg and Fe, as well as NSAIDs, at concentrations exceeding the limits established for aquatic life protection. These pollutants have been shown to induce oxidative stress on Cyprinus carpio and may therefore also damage the genetic material of exposed organisms, eliciting cytotoxicity as well. The present study aimed to determine the genotoxicity and cytotoxicity induced on blood, liver and gill of C. carpio by the pollutants present in MR water. Specimens were exposed to water from five sampling sites and the following biomarkers were evaluated: DNA damage by comet assay, frequency of micronuclei, apoptosis by TUNEL assay and caspase-3 activity. Significant increases relative to the control group ( P  < 0.05) were found with all biomarkers in all tissues evaluated, with the level of damage differing between sampling sites. In conclusion, pollutants present in MR water are genotoxic and cytotoxic to C. carpio, and this sentinel species, coupled with the biomarkers evaluated herein, is a reliable tool for assessing the health risk to wildlife posed by exposure to pollutants in freshwater bodies. Graphical abstract: Highlights: The Madín Dam is polluted by cytotoxic and genotoxic compounds, like heavy metals and pharmaceutical products. Cyprinus carpio is at risk in the Madín reservoir. Cytotoxicity and genotoxicity tests are a good tool to assess the risk of pollutants in water bodies.